Comprehensive care of patients with head injuries. Issue 6568 (7th February 1987) - Brocklehurst, G; Gooding, M; James, G
Abstract : The comprehensive head injury service run by the neurosurgeons at the Hull Royal Infirmary for the surrounding population of one million was analysed. The analysis showed that all patients with either a fractured skull or a lowered level of consciousness should be admitted to a district general hospital because the associated risk of their having a major head injury is over 20%. Those patients with both a fractured skull and a lowered level of consciousness have a 60% likelihood of a major head injury and should be transferred immediately to the neurosurgical unit. Patients with compound or complicated fractures of the skull and those without fractured skulls but with neurological impairment persisting for four hours or more, should also be transferred to the neurosurgical unit. If these guidelines are followed about 200 patients/million population will be referred to the neurosurgical centre. Patients with a minor head injury and none of the clinical risk factors may safely be sent home. This should reduce the rate of admissions to hospital for head injuries by 60%.